Теория и элементы систем автоматики - Шурыгин Ю. А. Юрий Алексеевич; Карпов А. Г. Андрей Геннадьевич; Зайченко Т. Н. Татьяна Николаевна; Целебровский И. В. Игорь Викторович; Коцубинский В. П. Владислав Петрович (Томск, Изд-во Томского ун-та, 2015)
В фонде НТБ ТПУ отсутствует